DINAMIKA EKSISTENSIAL KETHOPRAK BHAKTI KUNCORO KABUPATEN PATI DALAM ARUS MODERNITAS PASCA PANDEMI - Fajrie, Nur Fajrie; Zahro, Nabila Fatimatuz; Wijayanto, Wasis (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
Bhakti Kuncoro Kethoprak's art performance from Pati Regency, Central Java Province is interesting research. Based on the source of informants the head of the art group has faced existential challenges in maintaining and developing the traditional theatre art of kethoprak. This research aims to find out the strategies applied by Kethoprak Bhakti Kuncoro amid unhealthy art market competition between groups and how the significant impact of the COVID-19 pandemic affects the implementation of performances and the sustainability of traditional art groups in the era of modernity. A qualitative approach with a narrative type is used in the research by relying on empirical data from socio-cultural phenomena. Data collection was done through literature study, observation, and interviews. The results of this study include aspects of the existence of Kethoprak Bhakti Kuncoro involving the founding process, organizational structure during the performance, and factors that influence its existence. In addition, this research uses important elements in kethoprak, namely the play, dialogue actors, clothing, makeup, equipment, and musical accompaniment. Kethoprak functions as a ritual, entertainment, and a means of non-formal education through the values contained in the performance. This research is expected to make an important contribution to further understanding of the dynamics of traditional art groups amid changing times, as well as revealing the sustainability and adaptation of the Bhakti Kuncoro kethoprak group in Gunungsari Village, Batangan District, Pati Regency, Central Java Province.